Psychometric properties of the Stress and Anxiety to Viral Epidemics-9 scale among frontline nursing professionals working in the COVID-19 inpatients ward - Kim, Harin; Hong, Jihoon; Cho, Inn-Kyu; Lee, Dongin; Cho, Eulah; Jun, Jin Yong; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
This study examined the reliability and validity of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) scale among nursing professionals working in a COVID-19 inpatient ward. An anonymous, online survey was conducted among working frontline nursing professionals between April 7 and 18, 2022. We collected information about the participants’ age, sex, years of employment, shift work, and marital status. In addition, the participants were asked whether they had dealt with infected patients recently, and whether they had been quarantined, infected, or vaccinated. SAVE-9, Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9) were used to evaluate symptoms. We used the Confirmatory Factor Analysis (CFA) to determine the validity of the two-factor model of the SAVE-9 scale. We also tested reliability and convergent validity using the PHQ-9 and GAD-7 scales. A total of 136 responses was analyzed, and CFA for two-factors model of the SAVE-9 scale showed a good model fit among frontline nursing professionals (CFI = 1.000, TLI = 1.040, RMSEA = 0.000, RSMR = 0.060). Multi-group CFAs revealed that the SAVE-9 scale can measure work-related stress and viral anxiety in the same way across sex, having depression, or having generalized anxiety. The internal consistency was shown to be good, and the SAVE-9 scale was significantly correlated with the GAD-7 (r = .328, p < .001) and PHQ-9 score (r = .361, p < .001). The two-factor model of the SAVE-9 is a valid and reliable scale for frontline nursing professionals.